Carceral citizens rising: understanding oppression resistance work through the lens od carceral status - Woodall, Denise Ruth (Social service review, 2022)
We have all committed crimes, but few get caught. The distinction between carceral and conventional citizens is largely an illusion but one that affords great privileges to some and grave consequences for others. Rooted in critical feminist theorizing, intersectionality, and abolitionist scholarship, we extend Miller and Stuart’s conceptualization of carceral and conventional citizenship by embedding them in a social identity and system of power we call“carceral status” that intersects other categories like race, class, and gender. We draw from interviews with 32 formerly incarcerated activists to illustrate how carceral citizens experience “five faces of oppression” that define an oppressed group. Not only do they make material changes in institutions through their work, but they also symbolically restory themselves and transform the meaning of the carceral citizen category, providing new dignifying meanings to this aspect of identity. Our project introduces carceral status as a useful analytic tool for research and practice.